Antagonistic activity of immobilized symbiotics after lyophilization and storage at different temperatures - Shkarlat, Halyna; Cherkashyna, Yana; Stepanyuk, Ludmyla; Sevastianov, Stanislav (Problems of Cryobiology and Cryomedicine, 2022)
Probl Cryobiol Cryomed 2022; 32(4):308